Progress of Fire-dragon moxibustion therapy and nursing of shoulder-hand syndrome after stroke (中风后肩手综合征的火龙罐治疗及护理进展) - LIU Chunyan (刘春艳); YANG Yanni (杨燕妮); LUO Lihua (罗丽华); QIAO Lixiao (乔莉晓) (中西医结合护理)
This paper reviewed the study of Fire-dragon moxibustion therapy and nursing of shoulder-hand syndrome after stroke. The mechanism and operation method of Fire-dragon moxibustion therapy, as well as nursing cooperation, were summarized, in order to provide reference for clinical treatment and nursing practice. (本文总结中风后肩手综合征的火龙罐治疗及护理进展, 归纳了中风后肩手综合征的火龙罐治疗的作用机制、操作方法以及护理要点, 以期为火龙罐治疗肩手综合征的临床护理提供参考。)